Razvojni problemi podeželskih naselij Spodnjega Podravja - Korošec, Vladimir (Geografski vestnik, 2005)
Since 1991 rural settlements of Spodnje Podravje have been changing considerably due to growth of towns, increasing employment in non-agricultural branches, now local organisations or other similar processes of development. In the discussed region certain development area have differentiated within which central rural settlements are invigorated forming the local development nuclei. Characteristic are strong urbanisation of outskirts, central or other flatland settlements lying nearby important traffic roads, mixed husbandry structure of settlements in hilly parts as well as nearly perfect demographic and economic degradation of settlements within areas with difficult working conditions or near border region. Socio-economic typology of rural settlements has been made after careful analysis of demographic, economic and functional changes. All settlements within the discussed region have been arranged into 12 types or groups with regard to similar structure and development tendencies.
Keywords: družbena geografija; human geography; podeželje; rural area; regionalni razvoj; urbanizacija; Slovenia; Slovenija; Podravje